Light microscopy of microsporidian spores and baculovirus occlusion bodies in Epinotia aporema and Helicoverpa gelotopoeon larval tissues, respectively - Arneodo Larochette, Joel Demian; Taibo, Catalina Beatriz; Sciocco, Alicia Ines (2017)
Entomopathogens help regulate natural insect populations, and their use in pest management is the subject of active research. Classical and molecular techniques are currently available to elucidate disease etiology and pathogenesis. Here, we performed an Azan trichrome stain for light microscopic visualization of pathogens in the larval tissues of two Neotropical lepidopterans.